Peningkatan Minat Belajar Pendidikan Jasmani Melalui Modifikasi Cabang Olahraga Sepak Bola di Sekolah Dasar - Irwandi, Andi; Rizal, A.; Burhan, Burhan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to investigate increasing interest in learning physical education in elementary schools by modifying the sport of soccer. This research was carried out in elementary schools. Data collection techniques through processes. Pre-Intervention, Intervention, and Post-Intervention. This type of research uses a quasi-experimental design (quasi-experimental design). The collected data will be analyzed using appropriate statistical methods, such as testing the difference in mean values ​​between the treatment and control groups using the t-test or analysis of variance (ANOVA). In addition, further regression analysis can be used to see the relationship between other factors that influence interest in studying physical education. This research indicates that modifying the sport of soccer is a practical approach to increasing interest in learning physical education in elementary schools. Through an approach that is interesting, inclusive, and relevant to students' interests, the modification of the sport of soccer positively enriches physical education learning and shapes students' overall character. In conclusion, modification of the sport of soccer is a practical approach in increasing interest in learning physical education in elementary schools Keywords: Football, Interest in Learning, Modification